The Prufrockian Dynamicity of Resistance, Change and Acceptance in the Poetry of GhÄzÄ« Al-Quá¹£aybÄ« - Almahasheer, Muneerah B. (Asiatic: IIUM Journal of English Language and Literature, 2020)
While Modernism is recognised as originating in the United Kingdom and the United States, arising from conditions created by the Industrial Revolution and World Wars, the examination of Prufrockian Modernist elements in other cultural contexts can yield additional insights into the movement and readings of specific works. Though the Arab world is often considered through the lens of tradition and religion, issues of the modern world have also impacted the Arab culture, as in the work of contemporary Saudi poets, such as GhÄzÄ« Al-Quá¹£aybÄ« (1940-2010). As evident in the poems, themes and techniques found in conventional Modernist texts are also present in Al-Quá¹£aybÄ«â€™s work, within the Arabic context. Specifically, anxiety and alienation arising from the mechanisation of society as a result of the Industrial Revolution will be examined here. This study will, through the technique of comparison and contrast with the works of T.S. Eliot (1888- 1965) and Gertrude Stein (1874-1946), examine the claim that Al-Quá¹£aybÄ« â€˜s poetry accounts for a modernist shift observable through a change in the intensity with which objects are viewed within the Saudi cultural context. This intensity is in proportion to the industrial changes that have helped to reshape Arab society as well as the Saudi community. As in the Western context, the changes created through industrialisation have significantly impacted individualsâ€™ and indeed, entire cultures,â€™ experiences and romantic relationship with their environment and others, altering dominant expectations of the human experience.